ALTITUDINAL PATTERNS OF MYXOMYCETE DIVERSITY ACROSS TROPICAL FORESTS OF SOUTHERN VIETNAM - Y.K., Novozhilov; O.N., Shchepin; A.V., Alexandrova; E.S., Popov; N. H.A., Dagamac; Nguyen , Van Thinh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
ALTITUDINAL PATTERNS OF MYXOMYCETE DIVERSITY ACROSS TROPICAL FORESTS OF SOUTHERN VIETNAM In this paper, the fruit bodies of myxomycetes were collected in the field and were isolated from various substrates in humid chambers in the laboratory. The result showed that there is a high diversity of myxomycetes in the tropical forests of Vietnam. In totally, 159 species from 32 genera and 12 families developing on air and ground plant litter, rotten wood, feces of herbivorous animals, were identified with the 13 specially protected natural areas of Vietnam. In which, 69 taxa were firstly recorded in Vietnam. 4 new species were described. The result of the detailed comparative analysis using multivariate statistical methods was revealed some regularities of distribution of myxomycetes on a high-altitude gradient, biotopes, and also on various substrates. It is shown that: 1) the specieal diversity and abundance of myxomycetes are lower in mountain forests in comparison with plain forests, these indexes decrease inversely proportional to with altitude; 2) the abundance and specieal diversity of myxomycetes decrease by increasing the moisture of substrate; 3) There are differences in the species compositions between substrate groups of mountain forests and plain forests; 4) some common species in a temperate climate place have found in in the mountain tropical forests of Vietnam.